Mesoporous silica microparticles gated with a bulky azo derivative for the controlled release of dyes/drugs in colon. Issue 8 (15th August 2018) - Ferri, Daniel; Gaviña, Pablo; Parra, Margarita; Costero, Ana M.; El Haskouri, Jamal; Amorós, Pedro; Merino, Virginia; Teruel, Adrián H.; Sancenón, Félix; Martínez-Máñez, Ramón
Abstract : Mesoporous silica microparticles were prepared, loaded with the dye safranin O (M-Saf ) or with the drug budesonide (M-Bud ) and capped by the grafting of a bulky azo derivative. Cargo release from M-Saf at different pH values (mimicking those found in the gastrointestinal tract) in the absence or presence of sodium dithionite (a reducing agent mimicking azoreductase enzyme present in the colon) was tested. Negligible safranin O release was observed at pH 6.8 and 4.5, whereas a moderate delivery at pH 1.2 was noted and attributed to the hydrolysis of the urea bond that linked the azo derivative onto the external surface of the inorganic scaffold. Moreover, a marked release was observed when sodium dithionite was present and was ascribed to the rupture of the azo bond in the molecular gate. Budesonide release from M-Bud in the presence of sodium dithionite was also assessed by ultraviolet-visible spectroscopy and high performance liquid chromatography measurements. In addition, preliminary in vivo experiments with M-Saf carried out in mice indicated that the chemical integrity of the microparticles remained unaltered in the stomach and the small intestine, and safranin O seemed to be released in the colon.